First descriptions of the females of Cyclogomphus heterostylus Selys, 1854 and Ictinogomphus distinctus Ram, 1985 from India, with comments on the status of Cyclogomphus wilkinsi Fraser, 1926 (Odonata: Gomphidae) - Payra, Arajush; Tiple, Ashish D; Koparde, Pankaj (Zootaxa, 2023)
The present paper deals with the first descriptions of the females of two endemic Gomphid dragonflies of India, namely Cyclogomphus heterostylus Selys, 1854 and Ictinogomphus distinctus Ram, 1985, based on the specimens collected from Maharashtra, India. Additionally present status of Cyclogomphus wilkinsi Fraser, 1926 in India is also discussed.